2016
DOI: 10.1016/j.ebiom.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of Lysophosphatidic Acid Receptor 1 Reduces Cytokine Release and Protects Against Lung Injury

Abstract: Lysophosphatidic acid receptor 1 (LPA1) is a druggable target for treating pulmonary inflammatory diseases. However, the molecular regulation of LPA1 stability, a factor that critically impacts its biological activity, remains largely unknown. Here we identify two enzymes that regulate the balance of LPA1 ubiquitination and deubiquitination. Ubiquitin E3 ligase Nedd4L targets LPA1 for its site specific ubiquitination and degradation in the lysosome. Nedd4L negatively regulates LPA-LPA1-mediated cytokine releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…FBXL19 is a subunit of an SCF family E3 ubiquitin ligase, which exhibits an anti-inflammatory property (23); however, its substrates related to cytokine gene expression have not been identified. We tested whether FBXL19 regulated the protein stability of HATs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FBXL19 is a subunit of an SCF family E3 ubiquitin ligase, which exhibits an anti-inflammatory property (23); however, its substrates related to cytokine gene expression have not been identified. We tested whether FBXL19 regulated the protein stability of HATs.…”
Section: Resultsmentioning
confidence: 99%
“…S4A). We previously showed that the phosphorylation of substrates promotes their binding to E3 ubiquitin ligases (23). Thus, the phosphorylation of CBP may inhibit its interaction with FBXL19.…”
Section: Resultsmentioning
confidence: 99%
“…After all, the TLR4 agonist lipopolysaccharide (LPS) is a well-established tool for the induction of mucous hypersecretion as well as the host of associated osmoregulatory gene expression changes reported in the proposed Nedd4L ASO CF model. 17 Thus, as with previous efforts, interpretation of the reported data as a mechanistically-relevant, on target, and effective treatment of CF might be premature.…”
mentioning
confidence: 89%
“…After their receptor activation, cIAP-mediated K63-ubiquitination of RIPK1 and the TRAF proteins leads to the recruitment of linear ubiquitin chain assembly complex (LUBAC). The stability of lysophosphatidic acid receptor 1 (LPA1) is up-regulated by ubiquitin-specific protease 11 (USP11), which deubiquitinates LPA1 and enhances LPA1-mediated proinflammatory effects [33,[36][37][38][39]. Furthermore, the deubiquitinating enzyme USP13 stabilizes the anti-inflammatory receptor IL-1R8/Sigirr to suppress lung inflammation [40][41][42].…”
Section: Molecular Mechanisms Of Dubs In the Pathogenesis Of Ali/ardsmentioning
confidence: 99%
“…NLRP3 [38] Regulates NLRP3 inflammasome activation [38] NF-κB [39], NEMO [33] Regulates NF-κB signaling [33,39] VP24 [49] Involves in virus replication [49] Tat [50] Involves in virus production [50] TRAF3/TRAF6 [51] Modulates antiviral signaling [51] TRAF6/IKKγ [34] Regulates TLR signaling [34] USP-10 CFTR [37,52] Epithelial mucosal clearance [37,52] NICD1 [53] Regulates Notch signaling [53] USP-11 E2F1 [54] Regulates lung epithelia proliferation and wound healing [54] LPA1 [36] Enhances inflammation [36] USP-13 IL-1R8/Sigirr [40] Suppresses lung inflammation [40] PTEN [41] Regulates cell apoptosis [41] MCL1 [42] Regulates transformation of fibroblasts [42] STAT1 [55] Regulates IFN Signaling [55] STING [56] Negatively regulates antiviral responses [56] USP-14 I-kB [31] Increases cytokine release [31] CBP [32] Lung inflammation [32] USP-15 IκBα [57] NF-κB activation [57] USP-17 HDAC2 [58] Reverses glucocorticoid resistance [58] TRAF2/TRAF3 [59] Lung inflammation [59] [92] Inhibits type I IFN signaling and antiviral response [92] POH1 pro-IL-1β [93] Negatively regulates the immune response [93] BRCC3 NLRP3…”
Section: Dubsmentioning
confidence: 99%